Extend of Organisational Learning in Respect to Effective Implementation of Industrialised Building System (IBS) in the Construction Industry in Malaysia - Willibrord, Evangelyn (2007)
Since Malaysia’s independence 50 years ago, the construction industry in this country was at its infancy stage. Today, it is one of the contributors to the country's Gross Domestic Product. In construction, project experts hardly share knowledge in a structured manner; rather word of mouth is a common medium of disseminating information. Therefore, when the good people leaves the organisation or move to another project they bring with them the knowledge, experience and expertise. How do we introduce organisation that is involved inthe construction industry particularly contractors the concept of organisational learning? This paper looks at Malaysia's public and private sector readiness and challenges ahead to stop the brain drain of its existing skill sets, which will be dependent on available infrastructure and understanding of Malaysia’s learning organisation and organisational learning in the construction industry. Most importantly, whether Malaysia construction industry is one of a learning organisation to accept this changes and challenges and to study the impact of organisational learning to further promote the use of Industrialised Building System components nationwide for the very reason of changing the skill sets of labour, a more expensive skill sets due to most Malaysian being tertiary educated, the spiralling cost and shortage of labour, the ever increasing cost of conventional construction in raw materials and its efficiency.